Identification and quality of four varieties of adlay - Kesarin Lakkham; Preeya Wangsomnuk; Chantana Aromdee (Songklanakarin Journal of Science and Technology (SJST), 2009)
Simple methods were used to identify and evaluate the quality of adlay, which is currently in focus for its nutraceuticalaspect and functional food. Four varieties of adlay, Coix lachryma-jobi L., Poaceae, were investigated for their physicochemical properties, DNA fingerprints, antioxidant activities, and the content of coixenolide. They were called waxy adlay(AD1), stone adlay (AD2), grey adlay (AD3), and normal adlay (AD4). Morphology of intact seeds of the four varieties can be distinguished visually. Iodine stained on starch granules of all varieties, except AD4, were blue. The gelling temperaturesranged from 67.92-73.27oC. TLC-fingerprints of acetone and methanol were documented. DNA fingerprints were established to differentiate the varieties. AD1 showed distinct properties over the others in the antioxidant activities, acetone extractive and coixenolide content.